Rancangan Pengelolaan Sampah di Dusun Ngablak Rejo, Desa Gempolkurung, Kecamatan Menganti, Kabupaten Gresik - Dwi Rizza Khaironi (Universitas Airlangga, 2023)
Background: Garbage is a difficult problem to control. Factors affecting the waste problem is the development of the era which is not followed by the waste management knowledge. In Kabupaten Gresik, garbage problems arise from lack of final disposal capacity and poor knowledge of the waste impact. Therefore people manage their waste by burning, stockpiling, or dumping it into rivers. Objectives: This research aims to design the waste management system in Dusun Ngablak Rejo. Methods: The type of research used was descriptive by using case sudy design. Total population of this research was about 936 people from Dusun Ngablak Rejo. Purposive sampling was used to determine the reserach subject. Results: Based on analysis using system approach and community participatory, it was found that Dusun Ngablak Rejo had enough resources to do waste management properly. Counseling, advocacy, and FGD were conducted to improve awareness of residents in managing waste. The output of the process was the community leader had been chosen to be in charge in waste management of the community. Garbage transportation system will be handled by the residents with an agreed contribution amount of Rp 7,213 per month. The driver is a people of his own with a specified schedule. Karang Taruna participates as the person in charge of contribution fee collection. In August 2017, it has implemented 220 garbage bins, wheelbarrows with 2-wheeled motor vehicles, log books for each household and garbage bank. Conclusions: Continuous evaluation and monitoring needs to be done by the leader for the sustainability of the program.